2016
DOI: 10.1080/02701960.2016.1165218
|View full text |Cite
|
Sign up to set email alerts
|

Support workers as agents for health behavior change: An Australian study of the perceptions of clients with complex needs, support workers, and care coordinators

Abstract: An expanding aging population has placed increased demands on health care resources in many countries. Enhancing community aged care support workers' role to support greater client self-management and reablement is therefore timely. This article presents perceptions of the impact of an Australian practice change initiative designed to enhance knowledge, skills, and confidence of support workers to support behavior change in clients with complex health care needs. A comprehensive training program was delivered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…37, 1347-1352. https://doi.org/10.3109/09638288.2014.963707 Tables Table 1. Australian research mentions that 'reablement', developed and formalised since the 1990s, has focused on goal-or dementia. Such interventions have been described as a form of reablement (e.g., Cations et al, 2018; The book "Ageing in Australia" included a chapter "Care and Support for Older People" with a section on the more physical or mental health to help them accommodate their illness by learning or relearning the skills necessary for centred service and emphasised the necessity to develop an aged-care workforce of professionals capable to do th While restorative home care / reablement services for older adults have been "shown to be effective in reducing fu everyday activities, and quality of life" (Lewin et al, 2016: 807), the literature often focuses on support workers an collaboration (Lewin et al, 2016), to promote health-behaviour change (Lawn et al, 2017a), and to develop the ski A trend towards developing better collaboration is evident in a paper about the feasibility of LifeFul, a relationship care (Low et al, 2018). However, the authors stated that one of the main challenges to successfully implementing A critical review described reablement as "an emerging global practice model in community-and home-based care worldwide, researchers and policy makers still have questions about what reablement means and how it is used in wish to improve the functionality of clients so they can continue to live in their own homes; the authors concluded regrettable (Doh et al, 2019: 13).…”
Section: Statement Of Affiliation and Funding Supportmentioning
confidence: 99%
“…37, 1347-1352. https://doi.org/10.3109/09638288.2014.963707 Tables Table 1. Australian research mentions that 'reablement', developed and formalised since the 1990s, has focused on goal-or dementia. Such interventions have been described as a form of reablement (e.g., Cations et al, 2018; The book "Ageing in Australia" included a chapter "Care and Support for Older People" with a section on the more physical or mental health to help them accommodate their illness by learning or relearning the skills necessary for centred service and emphasised the necessity to develop an aged-care workforce of professionals capable to do th While restorative home care / reablement services for older adults have been "shown to be effective in reducing fu everyday activities, and quality of life" (Lewin et al, 2016: 807), the literature often focuses on support workers an collaboration (Lewin et al, 2016), to promote health-behaviour change (Lawn et al, 2017a), and to develop the ski A trend towards developing better collaboration is evident in a paper about the feasibility of LifeFul, a relationship care (Low et al, 2018). However, the authors stated that one of the main challenges to successfully implementing A critical review described reablement as "an emerging global practice model in community-and home-based care worldwide, researchers and policy makers still have questions about what reablement means and how it is used in wish to improve the functionality of clients so they can continue to live in their own homes; the authors concluded regrettable (Doh et al, 2019: 13).…”
Section: Statement Of Affiliation and Funding Supportmentioning
confidence: 99%
“…His randomized controlled trial based in Brazil demonstrated that CHWs as compared to trained counselors were equally effective in improving depression scores of patients. Lawn et al [ 68 ] found that lay support workers were an important part of an Australian care team and contributed to motivating complex patients to achieve behavioral change outcomes. Eli et al [ 69 ] conducted a randomized trial with Latino patients with evaluated depression and either heart disease or diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Lawn et al . () and Lawn et al . () examined future enhancement and skill development of the home support worker role.…”
Section: Introductionmentioning
confidence: 87%